2019
DOI: 10.3176/earth.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in the Caspian Sea wave climate in 2002–2013 from satellite altimetry

Abstract: The core properties of the wave climate and its changes in the Caspian Sea are established in terms of the annual mean significant wave height and its regional changes in 2002-2013 based on the outcome of the satellite altimetry mission JASON-1. Remotely estimated wave heights are validated against properties of the empirical distribution of instrumentally measured wave heights in the southern Caspian Sea and monthly averages of visually observed wave heights at three locations. A correction for systematic dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The extreme sea levels for different return periods (5,10,25,50, and 100 years) were calculated. The extreme sea level values in the northern part of the Caspian Sea for the return period of 100 years are close to 3 m; the areas with big surges are located along the eastern and western coasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme sea levels for different return periods (5,10,25,50, and 100 years) were calculated. The extreme sea level values in the northern part of the Caspian Sea for the return period of 100 years are close to 3 m; the areas with big surges are located along the eastern and western coasts.…”
Section: Discussionmentioning
confidence: 99%
“…They modified the coefficients of whitecapping and wave breaking based on the comparison of simulation and observational data, which reduced modeling errors for specific points and for a certain time period. Kudryavtseva et al (2016) showed the main features of the wave climate in the Caspian Sea for the 2002-2013 time period based on altimetry data [25]. It is not surprising that the results of the analysis and forecasting of waves highly depend on the quality of the wind data input.…”
Section: Introductionmentioning
confidence: 99%
“…Wave climate of the Caspian Sea based on NCEP/NCAR reanalysis presented in studies of [Lopatoukhin, 2019, Lopatukhin and Yaitskaya, 2018, Yaitskaya, 2017. The main features of the wave climate in the Caspian Sea based on altimetry data are displayed in [Kudryavtseva et al, 2019, Lama et al, 2022. The wave energy was estimated in [Amini et al, 2021, Kamranzad et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Wave climate of the Caspian Sea based on low-resolution NCEP/NCAR reanalysis is presented in [19,[23][24][25]. The main features of the wave climate in the Caspian Sea for 2002-2013 based on altimetry data are displayed in [26]. Detailed estimates of monthly mean satellite-based wave heights for the Caspian Sea are given in [27].…”
Section: Introductionmentioning
confidence: 99%